2021
DOI: 10.3390/ijms22073461
|View full text |Cite
|
Sign up to set email alerts
|

Microglia: The Missing Link to Decipher and Therapeutically Control MS Progression?

Abstract: Therapeutically controlling chronic progression in multiple sclerosis (MS) remains a major challenge. MS progression is defined as a steady loss of parenchymal and functional integrity of the central nervous system (CNS), occurring independent of relapses or focal, magnetic resonance imaging (MRI)-detectable inflammatory lesions. While it clinically surfaces in primary or secondary progressive MS, it is assumed to be an integral component of MS from the very beginning. The exact mechanisms causing progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 145 publications
1
39
0
Order By: Relevance
“…7,10 Similarly, the acute and chronic white matter lesions contribute independently to disease progression, implying that different mechanisms are likely to be responsible for acute and smouldering inflammation. 1,2,3,26,27 Finally, the gradient of tissue severity damage in NAWM and the presence of chronic active lesions are more prominent in patients with progressive forms of MS. 11,14 Therefore, it is plausible that some of the mechanisms proposed to explain the periventricular predominance of abnormalities in the NAWM, such as a neurotoxic effect of soluble CSF-derived factors, 12,28 hypoxia 29 , reduced remyelinating capacity 30 or increased compartmentalized inflammation 9 in periventricular region and microglial activation 12 are important mediators of the expansion of chronic lesions observed in our study.…”
Section: Lesion Expansion and Nawm Periventricular Gradientmentioning
confidence: 99%
“…7,10 Similarly, the acute and chronic white matter lesions contribute independently to disease progression, implying that different mechanisms are likely to be responsible for acute and smouldering inflammation. 1,2,3,26,27 Finally, the gradient of tissue severity damage in NAWM and the presence of chronic active lesions are more prominent in patients with progressive forms of MS. 11,14 Therefore, it is plausible that some of the mechanisms proposed to explain the periventricular predominance of abnormalities in the NAWM, such as a neurotoxic effect of soluble CSF-derived factors, 12,28 hypoxia 29 , reduced remyelinating capacity 30 or increased compartmentalized inflammation 9 in periventricular region and microglial activation 12 are important mediators of the expansion of chronic lesions observed in our study.…”
Section: Lesion Expansion and Nawm Periventricular Gradientmentioning
confidence: 99%
“…Microglia could transfer into neurotoxic microglia, which presents MHCII and CD86 by stimulating IL-6 and IFN-γ. Then, they produce cytokines such as NO, ROS, IL-1β, and TNF-α to promote oligodendrocyte damage ( Geladaris et al, 2021 ).…”
Section: Mechanisms Of Demyelinationmentioning
confidence: 99%
“…Indeed, Popovich et al (2002) demonstrated that direct activation of "CNS macrophages" (covering both invading peripheral macrophages and CNS resident microglia) results in axonal damage and demyelination. This conclusion has gained strong support over the past 20 years and activated microglia in particular seem to represent promising targets in MS (Geladaris et al, 2021). As described above, ASICs are functionally expressed in both macrophages and microglia, and contribute to their activation during periods of acidosis.…”
Section: Multiple Sclerosis and Other Neurodegenerative Diseasesmentioning
confidence: 74%
“…It has been known for some time that the severity of disease progression in MS patients is linked to microglial activation (Heppner et al, 2005;Jack et al, 2005;Geladaris et al, 2021), and it seems that microglial phagocytosis of stressed neurons contributes to neurodegeneration in AD, PD, ischemic stroke, CNS viral infections, and aging (Butler et al, 2021). Rat microglia have been shown to express ASIC1, ASIC2a and ASIC3.…”
Section: Acid-sensing Ion Channels In Microgliamentioning
confidence: 99%